Engineering Steels and High Entropy-Alloys - Sharma, Ashutosh; Duriagina, Zoia; Kumar, Sanjeev (IntechOpen, 2020)
"This book entitled "Engineering Steels and High Entropy-Alloys" presents an overview of various types of advanced steels and high entropy alloys. It also discusses the current research trends, problems, and applications of engineering steels and high entropy materials. The book also gives a brief overview of advances in surface protection strategies of steels and laser processing of materials (additive manufacturing). The various key features of this book include: 1. A comprehensive overview of various types of engineering steels, phase transformation, and applications in engineering. 2. A complete detailed understanding and mechanism of high entropy materials, including high entropy alloys and ceramics. 3. Descriptions of structure-property relationships in high entropy materials and their application in various fields such as biomedical implants. 4. A brief review of various laser processing (additive manufacturing) and surface protection of advanced materials."